Analysis of Irrigation Modernization Readiness Using FAHP Method - Berliana Larasati; Delvi Yanti; Rusnam Rusnam (The University of Lampung, 2025)
Irrigation modernization is a solution proposed to achieve an effective, efficient, and sustainable participatory irrigation management system. The purpose of this study was to measure the value of irrigation modernization readiness (IKMI) and determine the priority order of the Batang Anai Irrigation Area (IA). The IKMI method used 5 criteria for irrigation modernization (reliability of water supply, water and irrigation resource facilities and infrastructure, management of water and irrigation resources systems, water and irrigation resource management institutions, and human resources) and determines the priority order for modernization preparation using the Fuzzy Analytical Hierarchy Process method. Direct observation activities were carried out for the pillars of irrigation infrastructure and water availability, while interviews and questionnaires were used to assess management systems, management institutions, and human resources. The IKMI value 67.50 for the Batang Anai IA implies modernization is postponed, and irrigation system improvements can be carried out for 1-2 years. The priority order for irrigation modernization is water availability, management institutions, irrigation management, irrigation infrastructure, and human resources. Recommended actions for modernization readiness include checking the water supply system, normalizing irrigation channels, repairing damaged irrigation infrastructure, increasing farmer participation through socialization and training activities, and building synergy between irrigation managers. Keywords: FAHP, IKMI, Irrigation, Modernization, Sustainability.